2012
DOI: 10.1016/j.joen.2012.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Hypophosphatasia-associated Deficiencies in Mineralization and Gene Expression in Cultured Dental Pulp Cells Obtained from Human Teeth

Abstract: Introduction Mutations in the gene ALPL in hypophosphatasia (HPP) reduce the function of tissue nonspecific alkaline phosphatase, and the resulting increase in pyrophosphate (PPi) contributes to bone and tooth mineralization defects by inhibiting physiologic calcium-phosphate (Pi) precipitation. Although periodontal phenotypes are well documented, pulp/dentin abnormalities have been suggested in the clinical literature although reports are variable and underlying mechanisms remains unclear. In vitro analyses w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…Firstly, there was a heterozygous substitution C → T at position 454-nt, leading to the substitution of cysteine for arginine 152 (p.R152C), an alteration previously described in this family and found in the mother of the probands [18-20]. The p.R152C (c.454C>T) missense mutation, associated to other mutation p.R184W (c.550C>T), has been reported previously in a case of adult HPP (p.[R152C];[R184W]; SESEP – University of Versailles- Saint Quentin), whereas a mutation affecting the same codon p.R152H (c.455G>A) has been described in the mother of a patient with a lethal clinical form of HPP [28].…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…Firstly, there was a heterozygous substitution C → T at position 454-nt, leading to the substitution of cysteine for arginine 152 (p.R152C), an alteration previously described in this family and found in the mother of the probands [18-20]. The p.R152C (c.454C>T) missense mutation, associated to other mutation p.R184W (c.550C>T), has been reported previously in a case of adult HPP (p.[R152C];[R184W]; SESEP – University of Versailles- Saint Quentin), whereas a mutation affecting the same codon p.R152H (c.455G>A) has been described in the mother of a patient with a lethal clinical form of HPP [28].…”
Section: Resultsmentioning
confidence: 91%
“…We have demonstrated previously that primary periodontal ligament and dental pulp cells harvested from the same probands exhibited increased ALPL mRNA, whereas residual ALP activity and ability to promote mineralization in vitro were markedly reduced (40% and 50%, respectively) [18, 20]. Here, we showed that increased ALPL mRNA concentration in these cells does not result in increased protein expression, suggesting that regulatory mechanisms, such as the ER quality-control system, may be intervening and resulting in defective intracellular transport of mutant TNAP, likely due to retention of a fraction of mutant TNAP molecules in the intracellular compartment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Whether these cell changes contribute to dentin defects or arise as a result of them is under investigation. Recently we reported that pulp cells from HPP-diagnosed subjects were unable to acquire an odontoblast phenotype and to promote mineralization in vitro , which was partially restored by phosphate/PP i modulation (42). …”
Section: Discussionmentioning
confidence: 99%